Compréhension des perturbations accidentelles du mouvement dans l’activité dans une perspective de prévention - Sylvie Leclercq; Alain Garrigou (Activités)
Injuries resulting from a collision, a slip, a jam or any other accidental disturbance of voluntary movement represent more than 200,000 occupational accidents (OA) with days lost each year. This article is based on the combination of knowledge relating to occupational risk of accident with movement disturbance (AMD), movement in the activity and operational regulations with a view to understanding both the performance and the failure of movement control in the activity. Movement, inseparable from the activity of which it is a part, emerges from interactions in the occupational situation, just like activity. Its control simultaneously and inseparably targets the performance of the task and the avoidance of accidental movement disturbances. First of all the risk of AMD is characterized; the control of movement in the activity is then presented. The diversity of risk situations and its effect on prevention are then discussed, as are the variabilities in work situations, variabilities to which the regulations respond and from which the AMDs emerge. Time management in relation to the AMD risk is then illustrated using accident analyses. Finally, a framework focusing on the activity is proposed for analyzing movement in the activity in both usual and accidental situations.